Development of safety performance functions and crash modification factors for expressway ramps - Choi, Yoon Hwan; Park, Sung Ho; Ko, Hangeom; Kim, Kyung Hyun; Yun, Ilsoo (KSCE Journal of Civil Engineering, 2018)
The ramp is a typical section of expressway interchanges where design elements such as the grade and curvature complicatedly changes along the ramp. Dynamic changes in the design elements of ramps may seriously influence driving behaviors, resulting in more crashes on ramps than other freeway facilities. Therefore, there is a strong need to improve traffic safety of freeway ramps through in-depth studies regarding the effects of freeway design elements on freeway crashes. In this study, the crash data of 2007–2009 for expressway ramps, data associated with various ramp design elements, and the annual average daily traffic were collected. Using the data, three negative binomial regression models for the Safety Performance Functions (SPFs) were developed for individual ramp types, including direct, semi-direct, and loop types. Based on the SPFs, Crash Modification Factors (CMFs) were developed for selected design elements. For the validation of developed SPFs and CMFs, the frequency of traffic crash estimated using the SPFs and CMFs was compared with the actual frequency of traffic crashes. As a result, traffic crash prediction using the SPFs and CMFs was found out to be robust in general. The results of this study are expected to contribute to improving traffic safety on freeway ramps by quantifying the effects of diverse decision makings regarding ramp design elements on crashes.
Keywords: Crash prediction; Design elements; expressway ramp; Modification factors; Negative binomial regression model; Poisson regression models; crash modification factors; crash prediction model; design elements; expressway ramp; negative binomial regression model; Poisson regression model